EVIDENCE BASED CASE REPORT (EBCR) : PENGARUH PENERAPAN METODE KANGGURU TERHADAP KENAIKAN BERAT BADAN PADA BAYI BERAT LAHIR RENDAH (Jurnal Kesehatan Siliwangi, 2023)
Background: Neonates experience a gradual transition from intrauterine to extrauterine life which is characterized by limitations based on the maturation of organ functions. Newborns are currently at high risk of a number of health problems, one of which is low birth weight. The kangaroo method, also known as attached baby care, is a strategy to reduce LBW mortality and morbidity. The kangaroo method is an early care method that mimics the kangaroo by touching the skin of mother and child. Purpose: The effect of the kangaroo method on weight gain in newborns with low birth weight is the focus of this study. Method: This journal search method uses keywords, Boolean Operators and E-data based with. This type of research is literature review and experiment. Results: Based on these results, it was found that there was an effect of the kangaroo method on weight gain in low birth weight babies. Conclusion: It is hoped that health workers will use the kangaroo method to overcome the problem of babies born with low birth weight gaining weight as an easy and cheap alternative that can be found by the community.